Labor law cases and materials - Gorman, Robert A. (Indianapolis Bobbs-Merrill, 2017)
The Sixteenth Edition makes a number of significant changes to its predecessor, reflecting the evolution of the law relating to employers, employees, and unions in a dynamic economy. This edition includes new decisions of the National Labor Relations Board appointed by President Obama, which has departed in important ways from the approach of the Board under the prior administration. Moreover, the Board is now actively confronting the role of labor law in the contemporary workplace, addressing emergent issues such as protections for employee electronic communications and social media interactions, accountability for employers in ?fissured? enterprises, and potential limitations on other employer restrictions on collective activity. The book also contains judicial decisions addressing these developments as well as reactions in Congress and elsewhere, evincing the growing polarization over the role of labor unions in society.
Keywords: Labor laws and legislation--United States--Cases.